Recent Advances in Contact Mechanics Papers Collected at the 5th Contact Mechanics International Symposium (CMIS2009), April 28-30, 2009, Chania, Greece - Stavroulakis, Georgios E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Contact mechanics is an active research area with deep theoretical and numerical roots. The links between nonsmooth analysis and optimization with mechanics have been investigated intensively during the last decades, especially in Europe. The study of complementarity problems, variational -, quasivariational- and hemivariational inequalities arising in contact mechanics and beyond is a hot topic for interdisciplinary research and cooperation. The needs of industry for robust solution algorithms suitable for large scale applications and the regular updates of the respective elements in major commercial computational mechanics codes, demonstrate that this interaction is not restricted to the academic environment. The contributions of this book have been selected from the participants of the CMIS 2009 international conference which took place in Crete and continued a successful series of specialized contact mechanics conferences.
Keywords: Engineering; Mechanics; Materials; Mechanical engineering; Civil engineering; Engineering; Continuum Mechanics and Mechanics of Materials; Civil Engineering; Mechanical Engineering; Mechanics